2023
DOI: 10.1039/d3cc01428b
|View full text |Cite
|
Sign up to set email alerts
|

In situ growth of a GDY–MnOx heterointerface for selective and efficient ammonia production

Abstract: A heterostructured catalyst of GDY-MnOx was syntheiszed by controlled growth of MnOx on GDY. The incomplete charge-transfer between GDY and Mn atoms effectively increases the number of active sites, improves...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Compared with MnO 2 , the newly appeared peaks at 1382, 1589, 1912 and 2187 cm −1 corresponded to the D band, G band and alkynyl groups for GDY, respectively, which confirmed the successful synthesis of GDY/MnO x . 38 After the GDY was connected with MnO x , the obvious shift of the G band and conjugated diyne link modes towards higher wave numbers can be observed, indicating the strong chemical interaction (charge transfer or chemical bonding) between GDY and metal species. Besides, MnO x /GDY showed a larger I D / I G ratio than pure GDY, which indicated the increase of the defect sites after the combination of GDY and MnO x .…”
Section: Typical Structure Synthesis and Characterization Of Gdy/mosmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with MnO 2 , the newly appeared peaks at 1382, 1589, 1912 and 2187 cm −1 corresponded to the D band, G band and alkynyl groups for GDY, respectively, which confirmed the successful synthesis of GDY/MnO x . 38 After the GDY was connected with MnO x , the obvious shift of the G band and conjugated diyne link modes towards higher wave numbers can be observed, indicating the strong chemical interaction (charge transfer or chemical bonding) between GDY and metal species. Besides, MnO x /GDY showed a larger I D / I G ratio than pure GDY, which indicated the increase of the defect sites after the combination of GDY and MnO x .…”
Section: Typical Structure Synthesis and Characterization Of Gdy/mosmentioning
confidence: 99%
“…2a shows the in situ preparation process of the GDY–MnO x on a carbon cloth substrate. 38 Firstly, the GDY nanosheet was synthesized according to the previously reported Glaser–Hay coupling reaction. 40 Secondly, GDY–MnO x was synthesized via a one-step hydrothermal method.…”
Section: Typical Structure Synthesis and Characterization Of Gdy/mosmentioning
confidence: 99%
“…The eight electron transfer process associated electrochemical NO 3 − reduction reaction (NO 3 RR) to NH 3 is regarded as a promising means of converting NO 3 − without causing secondary contamination. 15,27–34 Nevertheless, it is possible to mitigate the competitive hydrogen evolution reaction (HER) by designing a suitable electrocatalyst. Transition metal organic complexes, including cobalt phthalocyanine (CoPc), 35,36 copper phthalocyanine (CuPc), 10,37 and nickel phthalocyanine-based composites, 14,38,39 are regarded as promising electrocatalysts where the transition metal center is the active center of the electrochemical reduction reactions and organic ring phthalocyanine inhibits the competing HER.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen in nitrate ions has an oxidation state of +5, which can form a number of nitrogenous products in oxidation states from +3 to −3, including nitrite (+3, NO 2 – ), nitric oxide (+2, NO), nitrous oxide (+1, N 2 O), nitrogen (0, N 2 ), hydroxylamine (−1, NH 2 OH), hydrazine (−2, N 2 H 4 ), and ammonia (−3, NH 3 ). , Development of numerous electrocatalytic systems using a variety of heterogeneous catalysts including Cu, Ag, Au, Rh, Ru, Ir, Pd, Pt, etc. often converts NO 3 – to N 2 via a five-electron transfer process. Several research groups have also shown that electrochemically NO 3 – can be converted to hydroxylamine, nitrite, and hydrazine. Electrocatalytic nitrate to ammonia conversion [NO 3 – + 6H 2 O + 8e – → NH 3 + 9OH – ] via an eight-electron transfer process using metal, nonmetal, and transition-metal-based electrocatalysts would be an alternative option for next-generation ammonia production. The selectivity toward ammonia synthesis was unsatisfactory, and generally a broad range of products is obtained. This is due to the complexity of the process, strong competition from HER, and the production of various byproducts, which reduce the faradaic efficiency (FE) and selectivity of ammonia .…”
Section: Introductionmentioning
confidence: 99%